Digestive findings that do not require endoscopic surveillance – Reducing the burden of care: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Rodríguez-de-Santiago, Enrique; Frazzoni, Leonardo; Fuccio, Lorenzo; van Hooft, Jeanin E; Ponchon, Thierry; Hassan, Cesare; Dinis-Ribeiro, Mário (Endoscopy, 2020)
With the aim of reducing the overall burden of care, ESGE recommends against surveillance of a series of conditions. Namely:ESGE recommends against surveillance of individuals with the following: an inlet esophageal patch; Los Angeles (LA) grade A or B erosive esophagitis; or < 1 cm columnar-lined esophagus.ESGE recommends against surveillance of those with intestinal metaplasia limited to the antrum unless additional risk factors are present, such as persistent Helicobacter pylori infection, incomplete metaplasia, or a family history of gastric cancer; or for fundic gland polyps in the absence of suspicious endoscopic features or hereditary syndromes.ESGE recommends against surveillance of gastrointestinal leiomyomas, lipomas, and antral pancreatic rests, provided that these lesions have typical ultrasonographic features.ESGE recommends against routine endoscopic surveillance in duodenal peptic ulcer, unless symptoms persist despite adequate therapy.ESGE suggests against surveillance of confirmed pancreatic serous cystic neoplasms.ESGE recommends against endoscopic surveillance for patients with hyperplastic polyps in the rectosigmoid, with 1 – 4 adenomas < 10 mm with low-grade dysplasia, or with a serrated polyp < 10 mm without dysplasia.ESGE recommends against surveillance of gastrointestinal conditions in individuals over 80 years old who have less than 10 years of life expectancy and poor general health status.